Guideline to Develop the Geography Teaching Proficiency for Social Studies Teacher - อินทรงค์, วัลลภา (Walailak Journal of Learning Innovations, 2021)
The development of Geography teaching proficiency for Social Studies teacher was the way to enhance teachers in all areas; knowledge, skills and teaching performances particularly in Geography parallel with the 21st century learning. It focuses on teaching for students understand the physical appearance of the world. The interaction between human and environment which leads to the creativity in their ways of life, awareness and environment changing adaptation. It can also adopt themselves along with the abilities to use geographical knowledge; skills, process, performances, and tools to arrange resources and environment that bring to lifestyle adaptation. Thus the educators may consider the key factors to develop their performances; 1) The competency of knowledge consists of knowing of Geography, Geographic skill, the competency of Geography and core curriculum of social study, religious and cultural subject. 2) The competency of learning management by geographic procedure consists of 5 steps are Geographic questioning, collecting information, managing information, criticizing and analyzing information and concluding to answer the question. 3) The competency of assessment and evaluation consists of the basic idea of authentic assessment and evaluation of Geography, the method of authentic assessment and evaluation of Geography and the definition or the situation of applying authentic assessment and evaluation. These following performances allow teachers to gain the awareness and skills for teaching Geography thoroughly. As the result, students can apply these knowledge and skills with their teaching performances successfully.